M4 Late asthmatic response to epoxy resins: a case report. (15th November 2016) - Solano, E; Fitzgerald, B; Cannon, J; Cullinan, P; Feary, J; Cajal, Ramon y
Abstract : Introduction: Epoxy resins (ER) systems are used extensively in industry in adhesives, reinforced plastics and surface coatings. ER are converted to the final product by mixing with a "hardener" or curing agent to form a polymer. This process releases fumes which can be respiratory sensitisers and a cause of occupational asthma (OA). Method: A non-atopic, non-smoker, 41 year old was referred with a six-month history of new onset asthma and 10 month history of nasal congestion and sneezing. His wheeze and dyspnoea occurred in the evenings and improved on holidays. He worked as a materials technician developing bonding agents and had started to use a new ER system one year previously. OA to the ER system was suspected and an in-patient specific inhalational challenge (SIC) performed. On day 1, a pre-treatment solution and a solvent (negative controls) were brushed on to a hard surface for 30 minutes. On day 2, the challenge was repeated using the same methods but with the addition of the ER system used at work. Histamine responsiveness 24 hours post challenge, FEV1 and symptoms were all monitored. At baseline FEV1 was 4.3L and bronchial response to histamine was normal (PC 20 16mg/ml). Blinding was not possible due to the patient's intimate knowledge of the products. Results: Exposure to the control agents induced no symptoms and no change in FEV1 or histamine responsiveness. Six hours after the active challenge FEV1 fell by 16% and the patient reported chest tightness and wheeze. 22 h post-challenge FEV1 reached a nadir of 2.0 L (52% fall) and bronchodilator therapy was administered (Figure ). Histamine responsiveness 24 h post challenge increased with a PC 20 of 3.3 mg/ml. The active challenge was not repeated. Conclusion: We demonstrated an isolated sustained late asthmatic reaction to the ER system confirming OA. The likely sensitiser was cyclohexylamine (an aliphatic amine hardener) which had a high "Chemical Asthma Hazard Assessment Score" of 0.9283. To ensure patient safety, it is important to be aware of this pattern of response (which is typical of low molecular weight agents). It also explains why the patient did not closely link his symptoms with work. The exact immunological mechanisms are not currently known.